Analysis of The Use “RSPWC Mobile” Online Registration Application in Complexity Perspective Patients BPJS in Pantiwilasa Citarum Hospital Semarang - Annisa Rakhmaningtyas; Sutopo Patria Jati; Rani Tiyas Budiyanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Long queue and waiting time in outpatient registration place at Pantiwilasa Citarum Semarang Hospital are becoming problems among BPJS patient. In order to solve this problem, Pantiwilasa Citarum Semarang Hospital develops an innovation of online based registration called RSPWC Mobile for androids. The innovation has not been utilized in maximum by BPJS patients. Thus, this research aims to determine the factors which are associated with the decision of usage for the application. This quantitative research are conducted with cross-sectional study. Questionnaire were given to 100 respondents or Patients with the criteria of those who have not yet used the RSPWC application and have medical record number. The data processing used is univariat and bivariat analytical method with chi square statistic test. The results of the study show that the variables which are signicifantly correlated to BPJS patients decision to use RSPWC mobile are relative advantages (p=0.016), compatibility (p=0.028), complexity (p=0.038), and observe abilities (p=0.009). The variable which is not significantly correlated is tested ability (p=0.322). The hospital is advised to add costumer care services menu for the users to give the feedbacks and the RSPWC Mobile application can saved files the first time are used to avoid repetition.